Futuristic Thinking Based On Organizational Culture For Visionary Leaders In Increasing The Competitiveness Of Educational Institutions - yulikah, Anik; Qomar, Mujamil; Masrokan Mutohar, Prim; Ambarwati, Ambarwati (CV. Inara, 2024)
This research is motivated by the phenomenon of many leaders of educational institutions who have difficulty increasing the competitiveness of their institutions, and this has a big impact on the sustainability of their institutions in the future. Visionary school principals have the opportunity to overcome these competitiveness problems by always developing various vision-based advantages and strengthening them into organizational culture so that their institutions are able to have competitive advantages. The question in this research is what form of implementation of futuristic thinking does the school principal take as a leader in increasing the competitiveness of educational institutions? This research took research locations at MAN 2 Tulungagung and SMK Muhammadiyah 7 Gondanglegi Malang using a qualitative research approach and case study research type. The results of this research show that: 1) the heads of MAN 2 Tulungagung and SMK Mutu Gondanglegi Malang have futuristic thinking skills, demonstrated by their ability to develop visions into strategic policies and programs to position their institutions in the future. Among the strategic policies are: a) Strengthening religious culture; b) strengthening academic culture; and c) strengthening non-academic culture. The conclusion of the results of this research shows that the futuristic thinking skills possessed by visionary school principals based on organizational culture have been able to increase the competitiveness of educational institutions.